2009
DOI: 10.1063/1.3116558
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced magnetic properties of FePt nanoparticles codeposited on Ag nanoislands

Abstract: Ag nanoislands have been used as nucleation sites for FePt nanoparticles when deposited on SiO 2 surfaces by electron beam evaporation. We demonstrate that it is possible to nucleate FePt nanoparticles on predeposited Ag clusters and that this results in a significant improvement of the hard magnetic Ag/FePt nanoparticles' properties. We find that, besides the usual annealing treatments, a simple predeposition of Ag nanoclusters promotes the formation of the FePt L1 0 phase at larger FePt nominal thicknesses ͑… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…One of the problems pointed out in these investigations was the need of high temperature annealing ( $ 600 1C) for making the as-sputtered A1 structure ordered to the L1 0 structure [4]. To reduce this kinetic ordering temperature, various additives have been investigated using continuous polycrystalline films [7][8][9][10][11][12][13][14], and Cu and Ag had been found to be effective in reducing the ordering temperature.…”
Section: Introductionmentioning
confidence: 98%
“…One of the problems pointed out in these investigations was the need of high temperature annealing ( $ 600 1C) for making the as-sputtered A1 structure ordered to the L1 0 structure [4]. To reduce this kinetic ordering temperature, various additives have been investigated using continuous polycrystalline films [7][8][9][10][11][12][13][14], and Cu and Ag had been found to be effective in reducing the ordering temperature.…”
Section: Introductionmentioning
confidence: 98%
“…Similar to gold, Ag atoms are immiscible with both Fe and Pt atoms. Ag has been added to FePt thin films to accelerate the L 1 0 ordering or promote crystallographic orientation. Ag doped FePt NPs have also been fabricated by chemical or physical methods. In these synthetic routes, the FePtAg nanoparticles often possess the fcc structure, and a post annealing process is needed. It has been demonstrated that the fcc–fct phase transition temperature for FePt NPs could be reduced by 100–150 °C via doping with silver. , However, reports on the one-step chemical synthesis of fct FePt NPs by using silver as a dopant remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the fcc FePt can be produced by both physical and chemical methods. The physical vapor deposition (PVD) method has been extensively studied for FePt nano alloyed films with high quality and less defects, 25–29 which can be a good candidate for information storage. However, it usually consumes a long time and calls for precious control.…”
Section: Controllable Synthesis Of Fe-based Nanoalloysmentioning
confidence: 99%